A systematic realist synthesis of digital interventions for enhancing mental health at work: contexts, mechanisms, and outcomes - Josefina Peláez Zuberbuhler; Luca Pietrantoni; Greta Mazzetti; Marco De Angelis; Davide Giusino; Mabel San Román-Niaves; Dina Guglielmi; Marisa Salanova (International Journal of Mental Health Systems)
Abstract Background Digital interventions (DIs) have emerged as promising tools for promoting mental health in the workplace. However, evidence on if, how, and under what circumstances they affect positive outcomes requires elucidation. This systematic realist review aimed to synthesize current knowledge on contexts, mechanisms, and outcomes of workplace DIs to enhance mental health at work. Methods The review integrates elements of both systematic and realist review methodologies. Forty-four workplace mental health DIs studies were gathered through a systematic electronic search using PsycNet, Scopus, Web of Science, and PubPsych. Results Results showed that demographics, previous mental health, and personal skills were the main individual context factors influencing the success of DIs. Key mechanisms were DIs usage, frequency, adherence, and relevance of content triggering positive perceptual shifts. Results showed improvements in psychological resources, wellbeing, and affect. Reduced ill-health symptoms were also evidenced. Five propositions were developed on the contexts and mechanisms under which digital interventions yield positive outcomes for mental health at work. Conclusions This study highlights several areas where future research can expand our understanding of DIs in the workplace by examining interactions between mechanisms and cultural aspects influencing implementation.